2009
DOI: 10.1182/blood-2008-10-186890
|View full text |Cite
|
Sign up to set email alerts
|

Human plasmacytoid dendritic cells are unresponsive to bacterial stimulation and require a novel type of cooperation with myeloid dendritic cells for maturation

Abstract: Dendritic cell (DC) populations play unique and essential roles in the detection of pathogens, but information on how different DC types work together is limited. In this study, 2 major DC populations of human blood, myeloid (mDCs) and plasmacytoid (pDCs), were cultured alone or together in the presence of pathogens or their products. We show that pDCs do not respond to whole bacteria when cultured alone, but mature in the presence of mDCs. Using purified stimuli, we dissect this cross-talk and demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
102
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 37 publications
8
102
1
Order By: Relevance
“…First,the composition of the studied particulates(apoptotic cells, beads, bacteria, or PLGA microparticles) is diverse and uptake might require different receptors and uptake mechanisms, some of which may not be exploited by pDCs. Furthermore, some studies compared the phagocytic capacity of pDCs to that of moDCs and found that pDCs showed very little to no uptake compared with moDCs (3,14,18). We also found that moDCs were superior to pDCs in phagocytosing particulate Ag, notwithstanding that almost all pDCs engulfed particles.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…First,the composition of the studied particulates(apoptotic cells, beads, bacteria, or PLGA microparticles) is diverse and uptake might require different receptors and uptake mechanisms, some of which may not be exploited by pDCs. Furthermore, some studies compared the phagocytic capacity of pDCs to that of moDCs and found that pDCs showed very little to no uptake compared with moDCs (3,14,18). We also found that moDCs were superior to pDCs in phagocytosing particulate Ag, notwithstanding that almost all pDCs engulfed particles.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, we investigated whether pDCs can play a role in immune responses against exogenous particulates. Up to now, it was highly controversial whether pDCs are able to respond to stimuli entrapped in particle-like structures (3,8,9,14,(16)(17)(18)(19). We demonstrate that pDCs are clearly capable of phagocytosing Ag entrapped within PLGA microparticles and subsequent processing of the encapsulated Ag.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations